LOW VISION IN RETINITIS PIGMENTOSA: HOW TO ENHANCE FUNCTIONAL VISION IN PSEUDOPHAKIC PATIENT: Poster Presentation - Case Report - Resident - Siti Shalihah Ramadhani Novizar; Ani Ismail; Eva Kumalasari (Majalah Oftalmologi Indonesia, 2023)
Introduction : Retinitis Pigmentosa (RP) could lead to various visual impairments, including decreased visual acuity, poor dark adaptation, decreased contrast sensitivity, poor color vision, visual field constriction, leading to low vision (LV). LV in RP decreases patient’s quality of life (QoL) and Independence. We aim to report a successful case of LV management in a bilateral pseudophakic patient with RP. Case Illustration : A 33-year-old man came with progressively blurred vision in both eyes (BE) that worsen 6 months ago. Ophthalmologic examination revealed his uncorrected visual acuity for right eye (RE) and left Eye (LE) was 6/60 and 4/60. The patient had cataract surgeries and IOLs implantation on BE in 2021. Funduscopic examination revealed the bone spicule appearance, blood vessel attenuation, and waxy disc pallor on BE. Humphrey's examination showed a peripheral visual field defect. Decreased contrast sensitivity and poor color vision were also found. Discussion : The patient was managed by LV aids and rehabilitation. Spectacle clarified distant and near vision with best corrected visual acuity (BCVA) 6/21 and 0.8 M on BE, photochromic lenses aided in adapting to various lighting levels and as a UV protection, and the addition of illumination and color contrast enhancement improved vision in dim light. A convex mirror to be used as a field- enhancement spotting tool. Rehabilitation enhances his head tracking, scanning, and habitual spotting skills. Improvement of QoL has been recorded using LVQoL questionnaires. Conclusion : LV management are vary based on an individual’s level of functional vision and personal preferences. Optimal LV management could enhance patient QoL and Independence.